Elaboração e caracterização do queijo tipo cottage adicionado de óleo de Pequi (Caryocar coriaceum Wittm.) - Borges, Otilia Mônica Alves (2016)
Pequi (Caryocar coriaceum Wittm) is an oleaginous pulp fruit found in the Cariri region, in Ceará. The oil extracted from the fruit has a high content of unsaturated fatty acids, so it can be used in foods to replace saturated fat of animal origin, such as found in dairy products. This study aimed to elaborate and characterize cottage cheese added with pequi oil. Eleven formulations were prepared according to an experimental design of the CCRD type (Central Composite Rotational Design), with two independent variables and two levels (pequi oil concentrations with 7 and 13% and emulsifier concentrations of 1 and 2%), having as variable answer the texture profile of the cheese. The dressing, creamy liquid that is added to the cheese, consisted of fermented milk, pequi oil and emulsifier. The final product was characterized by physical, chemical and physicochemical analysis (pH, acidity, fat, protein, moisture, color and texture profile). In addition, the antimicrobial activity of pequi oil against the microorganisms Staphylococcus aureus (ATCC 27644), Escherichia coli (ATCC 25922), Salmonella enteretidis (IAL 1132) and Listeria monocytogenes (ATCC 1911) was evaluated, using the antibiotic gentamicin as positive control. The raw materials used in the preparation of the products, milk and pequi oil, were within the standards required by Brazilian legislation. The concentrations of pequi oil and emulsifier at the levels studied influenced the parameters of fat, moisture, pH and color of cottage cheese. In the texture profile analysis, the cohesiveness and adhesiveness parameters were significant, with valid statistical models. No antimicrobial effect of pequi oil was observed, possibly because oil extraction conditions are required to obtain bioactive compounds with antimicrobial capacity. It is concluded that the elaboration of cottage cheese with the addition of pequi oil and emulsifier produces a product with physical, chemical and physicochemical characteristics similar to those obtained in other studies. In addition, the formulated cheeses presented characteristics that classified it as a skimmed and/or low-fat product that contains unsaturated fatty acids. Finally, cottage cheese added from pequi oil brings benefits to groups of people with restriction to saturated fat, besides being an alternative for the use and valorization of the fruit produced in the Region of Cariri, in Ceará.